THE DEVELOPMENT OF GLOBALIZATION OF WESTERN CULTURES: THE RESPONSES OF LIPIA STUDENTS TO HALLOWEEN CELEBRATION IN RIYADH - Regita Ardhea Dhea; Hening Chesharine Sakinah; Muhammad Nawawi (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
Westerners often talk about freedom of life in the modern era, including the Arab region which has begun to follow western cultural developments regarding modernization. Halloween is one of the celebrations held in Riyadh. By using a qualitative descriptive method, namely by analyzing the facts related to this information based on literature research from journals and articles as well as the results of questionnaires from LIPIA Jakarta students about Halloween in Riyadh, so that it is clear what LIPIA Jakarta Students think about the pros and cons. Thus, the outcome of Halloween in Riyadh is media conjecture, as the setting and feel coincides with Halloween celebrations in the west.